Learning style and academic performance of optometry students / Ai-Hong Chen and Ainin Nazrin Ahmad Nazri - Chen, Ai-Hong; Ahmad Nazri, Ainin Nazrin (Universiti Teknologi MARA, 2021)
There has been substantial research undertaken to relate the learning style to academic performance. Several studies have documented that multimodal or kinaesthetic was dominant in learning styles among university students. The effects of ethnicity and gender on the learning style in Optometry students have also been reported. However, the impact of learning style preference on academic performance in Optometry students has yet to be understood. This study aims to explore the relationship between learning style and academic performance among Optometry students. All 141 full-time optometry students were approached to participate in an online survey. Data on the learning styles were collected using the VARK questionnaire (VARK is an acronym for visual, aural, read/write, and kinesthetic learning modalities). The academic performance was based on the academic transcript and self-reporting competency. The response rate was approximately 83%. Our findings showed that the kinaesthetic learning style was predominant. 88% of the learning style was unimodal, and only 12% bimodal. No trimodal or quadrimodal was found. A possible explanation might be due to the gender composition in our respondents, of whom 82.5% were females. Females have been reported to prefer unimodal learning. These findings can contribute to a better understanding of learning styles to assist pedagogy teaching alignment in optimizing strategic teaching planning in the Optometry program. As a result of these investigations, suggestions were identified for future research.